HUBUNGAN KOMPETENSI PEDAGOGIK DAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN PROFESIONALITAS GURU DI PERGURUAN MUHAMMADIYAH CIPONDOH TANGERANG - Suhelmi Suhelmi; Suherman Suherman; Syadeli Hanafi (http://jurnal.untirta.ac.id/index.php/JTPPm, 2021)
The purpose of this study was to determine and analyze the relationship between pedagogic competence and principals' leadership with teacher professionalism. This type of research is a quantitative field research with a correlational approach. This research was conducted at the Cipondoh Muhammadiyah College, Tangerang. The population in this study were teachers at the Muhammadiyah College Cipondoh Tangerang with a total sample of 85 teachers. The results sH0wed that: 1) Based on the results of the analysis, it was concluded that there was a relationship between pedagogical competence and teacher professionalism at the Muhammadiyah College of Cipondoh Tangerang City, with rcount > rtable (0.284 > 0.213) and Sig value < value (0.000 < 0.05); 2) There is a relationship between the principal's leadership and teacher professionalism at the Cipondoh Muhammadiyah College, Tangerang City, with rcount > rtable (0.240 > 0.213) and Sig value < value (0.000 < 0.05); 3) There is a relationship between Pedagogic Competence and Principal Leadership together with teacher professionalism at the Cipondoh Muhammadiyah College, Tangerang City with an rcount > rtabel (0.329 > 0.213) and together the pedagogical competence and leadership of the principal contributed 10, 8% of the professionalism of teachers at the Cipondoh Muhammadiyah College, Tangerang City.Keywords: Pedagogic Competence, Principal Leadership, Teacher Professionalism